The Power of Implementing People's Business Credit Agreements at the BRI Tolitoli Unit (a Legal Analysis) - Ahmad Malontu (MultiTech Publisher, 2023)
People's Business Credit is a government program to help the people to increase their business. from Bank Rakyat Indonesia in overcoming the consequences that will arise and how to overcome or solve the problem. The results showed that the implementation of people's business loans to BRI units in Tolitoli Regency went through several stages, namely the application stage, the credit inspection or analysis stage, the granting of a decision, and the credit contract/credit disbursement stage. Legal issues arising from the provision of people's business loans are the existence of problem loans and the absence or lack of caution on the part of creditors and also customers who do not pay attention to fulfilling their monthly credit installment obligations.